ANALISIS RISIKO KEUANGAN DI ERA DIGITAL PADA USAHA SALAK DI PINRANG (STUDI KASUS PADA SURYA SALAK MAJENE): ANALISIS RISIKO KEUANGAN DI ERA DIGITAL PADA USAHA SALAK DI PINRANG (STUDI KASUS PADA SURYA SALAK MAJENE) - Dita Natasia; Siti Ismi Salsa Difa; Chici Asmiranda; Nur Intan (LP2M IBK Nitro, 2026)
This study aims to develop a contextual digital marketing model for MSMEs in the city of Medan by emphasizing the integration of digital technology and local cultural values. Employing a qualitative case study approach, the research involved ten MSME actors in the culinary sector through semi-structured interviews, participatory observation, and digital documentation analysis. Thematic analysis revealed four main themes: digitalization as a space for small business existence, honesty and locality as marketing identity, self-taught creativity as a key resource, and limited digital literacy. The findings indicate that culture-based strategies and social interaction can enhance digital trust and the competitiveness of MSMEs. Theoretically, this study strengthens the application of the Resource-Based View (RBV) and Customer Relationship Management (CRM) within a local context, while also providing a policy foundation for strengthening culture-based digital ecosystems.